Strategi Guru dalam Pengelolaan Pojok Baca untuk Menumbuhkan Minat Baca Siswa di SD Muhammadiyah Sangatta Utara - Nur Afni Pratiwi; Tri Velyna; Imam Syafi'i (Civiliza Publishing, Indonesia., 2026)
This study examined teacher strategies for managing a classroom reading corner to foster students' reading interest at SD Muhammadiyah Sangatta Utara. The research employed a descriptive qualitative field-study design. Data were obtained through observation, semi-structured interviews, and documentation involving the principal, three second-grade classroom teachers, and selected students. Data analysis followed the stages of data condensation, data display, and conclusion drawing, while credibility was strengthened through source and technique triangulation. The findings showed that reading-corner management was implemented through attractive and accessible spatial arrangement, provision of age-appropriate illustrated books, scheduled reading before lessons, independent and shared reading, storytelling and read-aloud activities, retelling, simple post-reading tasks, individual assistance, motivation, and teacher supervision. The school supported the program by providing shelves and books, allocating operational funds and committee assistance, allowing classroom teachers to adapt management to student characteristics, and conducting periodic supervision. Supporting factors included school policy, teacher creativity, comfortable classroom conditions, student enthusiasm for illustrated stories, and collaboration among school personnel. Inhibiting factors involved limited collection variety, uneven beginning-reading skills, home gadget use, restricted instructional time, and the need for intensive assistance. Teachers responded through book rotation, differentiated guidance, flexible scheduling, short literacy routines, varied activities, and continuous encouragement. The reading corner contributed to greater student interest, voluntary book use, emerging independent reading habits, improved comprehension and retelling, increased confidence, and more active classroom literacy participation. The study concludes that a reading corner becomes effective not merely because books are present, but because teachers transform it into an active literacy environment through systematic planning, meaningful routines, responsive assistance, and sustained school support.